2011
DOI: 10.1007/s11771-011-0892-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of vibrations induced by excavation of deep-buried cavern and open pit with method of bench blasting

Abstract: The measured data of vibrations induced by excavation of deep-buried cavern and open pit with method of bench blasting were analyzed by Fourier Transform and Wavelet Transform, and the characteristics of vibrations induced under these two circumstances were studied. It is concluded that with the similar rock condition and drilling-blasting parameters, vibration induced by bench blasting in deep-buried cavern has a higher main frequency and more scattered energy distribution than that in open pit. The vibration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…It is found by Wang and Huang, and Xu et al that, release rate and dynamic disturbance have great influence on the occurrence and extent of rockburst [28,29]. Our preparatory work also indicated that the transient release of in-situ stress induced release wave plays an important part in total vibration in surrounding rock mass [30,31].…”
Section: Introductionsupporting
confidence: 61%
“…It is found by Wang and Huang, and Xu et al that, release rate and dynamic disturbance have great influence on the occurrence and extent of rockburst [28,29]. Our preparatory work also indicated that the transient release of in-situ stress induced release wave plays an important part in total vibration in surrounding rock mass [30,31].…”
Section: Introductionsupporting
confidence: 61%
“…e PPV is larger in the dolomite than in the shale for a constant scaled distance. Lu et al [30] reported that the total energy of a blast-induced seismic activity is directly proportional to the square of the PPV during the same blasting. erefore, more explosive energy was converted to rock mass vibration in the dolomite bench than that in the shale bench.…”
Section: Attenuation Law For the Ppv Of Blasting Vibrationmentioning
confidence: 99%
“…Whereas, for the open-pit blasting, the time-energy density curve only has one peak group. Studies by Lu et al. (2011) shown that the two excitation sources are induced not by the delay errors of detonators but the blasting load and TRIS.…”
Section: A Practical Application Of Prediction Modelmentioning
confidence: 99%
“…Figure 12 shows that for each single delay, vibration has two dominant frequencies, and without exception, 180 Hz is their identification point. However, for the case of open-pit blasting, vibration has only one dominant frequency (Lu et al., 2011). This indicates that the coupled vibrations which have two dominant frequencies originate from the two excitation energy sources, the blasting load and TRIS.…”
Section: A Practical Application Of Prediction Modelmentioning
confidence: 99%
See 1 more Smart Citation